2017
DOI: 10.1152/jn.00795.2016
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on classical controversies about the motor cortex

Abstract: Primary motor cortex has been studied for more than a century, yet a consensus on its functional contribution to movement control is still out of reach. In particular, there remains controversy as to the level of control produced by motor cortex ("low-level" movement dynamics vs. "high-level" movement kinematics) and the role of sensory feedback. In this review, we present different perspectives on the two following questions: What does activity in motor cortex reflect? and How do planned motor commands intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
96
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(104 citation statements)
references
References 248 publications
(267 reference statements)
7
96
1
Order By: Relevance
“…More recently, Dietrichsen et al also found fMRI evidence, which confirms that large portions of the motor cortex represent complex muscle synergies in humans too (Ejaz 2015). These findings are in agreement with the functioning of so called corticomotoneuronal cells that have connections to multiple muscle groups to facilitate represent complex movement actions (Omrani 2017). These corticomotoneuronal cells are, however, confined to the evolutionary younger subdivision of M1, the Brodmann area BA4p which is the inferior portion of M1 on the pre-central bank of the central sulcus Strick 2006, 2009;Lemon 2008).…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…More recently, Dietrichsen et al also found fMRI evidence, which confirms that large portions of the motor cortex represent complex muscle synergies in humans too (Ejaz 2015). These findings are in agreement with the functioning of so called corticomotoneuronal cells that have connections to multiple muscle groups to facilitate represent complex movement actions (Omrani 2017). These corticomotoneuronal cells are, however, confined to the evolutionary younger subdivision of M1, the Brodmann area BA4p which is the inferior portion of M1 on the pre-central bank of the central sulcus Strick 2006, 2009;Lemon 2008).…”
Section: Introductionsupporting
confidence: 68%
“…The current state of consensus in the field is nicely summarized by Paul Cheney in (Omrani 2017; see also references therein); Overall, corticomotoneuronal cells in the primary motor encode muscle-related parameters of movement such as muscle activity and muscle force. Although some corticomotoneuronal cells in the primary motor cortex (particularly those involved with finger movements) have their terminations confined to motoneurons of single muscles, a large amount of corticomotoneuronal cells are not rigidly coupled to the activity of its target muscles but show specialization for particular movements or categories of muscle activity.…”
Section: Discussionmentioning
confidence: 99%
“…The relevant time scale for temporal coding by spike timing in the somatosensory cortex seems to be within tens of milliseconds from the stimulus, and the analysis requires extremely precise information about stimulus onset time 46,51,52 , which is not available in our naturalistic experimental paradigm. More generally, structured population dynamics in vibrissa motor cortex aligns well with other observations of population coding in motor cortex, where the population activity vector of both preparatory 53 and movementrelated activity 54,55 correlates with movement features [56][57][58] .…”
Section: Population Patterns In Cortical Networksupporting
confidence: 85%
“…It is unclear whether this finding affects our chosen ROIs. Some studies have reported widespread correlations with force across motor areas (Dai, Liu, Saghal, Brown, & Yue, ; Omrani, Kaufman, Hatsopoulos, & Cheney, ), while in other cases, the only reported region that overlapped with our ROIs was M1 (Ward & Frackowiak, ; Ward, Swayne, & Newton, ). To our knowledge, no study thus far has considered the effect of force of movement on effective connectivity within the cortical motor network.…”
Section: Resultsmentioning
confidence: 68%